Organizational citizenship behaviour relationship on challenge stress, hindrance stress and turnover intention in hotel industry employees in Java island - Prasetio, Kumala Hasta; Hendarsjah, Hidajat (Jurnal Konseling dan Pendidikan, 2024)
The high employee turnover rate in the hotel industry on Java Island, influenced by work stress and organizational behavior, poses a significant challenge to operational sustainability and service quality in this sector.This study examines the relationship between Organizational Citizenship Behavior (OCB), Challenge Stress (CS), Hindrance Stress (HS), and Turnover Intention (TI) among employees in the hotel industry on Java Island. The research investigates the distinct roles of OCB at the individual level (OCBI) and organizational level (OCBO) in influencing stress perceptions and employee turnover intentions. A quantitative approach was utilized, involving 220 hotel employees from various regions in Java. Data was collected using online questionnaires and analyzed using Structural Equation Modeling (SEM) with the SmartPLS tool. The findings reveal that OCBO significantly influences CS positively and HS significantly, while OCBI does not significantly impact either type of stress. Furthermore, HS has a strong positive effect on TI, whereas CS shows no significant impact. Interestingly, OCBO also exhibits a direct positive influence on TI. These results suggest that while OCB behaviors can enhance organizational functioning, they may also inadvertently contribute to stress and turnover intentions, especially when organizational support is insufficient. This study highlights the nuanced effects of OCB in the high-pressure context of the hotel industry. Practical implications include the need for organizations to balance employee contributions with adequate rewards and stress management strategies. Future research should explore additional moderating factors, such as organizational culture and job resources, to better understand the dynamics of stress and turnover in the hospitality sector